2016
DOI: 10.1007/s00265-016-2190-3
|View full text |Cite
|
Sign up to set email alerts
|

A classic question revisited in red-winged blackbirds: disentangling confounding hypotheses surrounding parental investment theory and nest defense intensity

Abstract: ) who 34 made our research possible. We also thank data proofers/entry (J. Whitaker, A. Blackert, S. 35Ramakrishnan). We are grateful to anonymous reviewers and to D. Westneat and P. Porneluzi for their 36 reviews that greatly improved our manuscript. 37 AbstractThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Female barnacle geese plastically increased their nest defence over the season, as reflected by a decrease in their FID. Parental investment theory and the renesting potential hypothesis are two non‐exclusive explanations for this pattern (see Introduction; Shew et al., 2016). Arctic‐breeding birds such as barnacle geese experience a very short breeding season, as the snow‐free season is limited (mean snow‐free season length in Kongsfjorden is 81 days ± 12: Lameris et al., 2019) which seems to prohibit renesting (from laying till fledge takes approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female barnacle geese plastically increased their nest defence over the season, as reflected by a decrease in their FID. Parental investment theory and the renesting potential hypothesis are two non‐exclusive explanations for this pattern (see Introduction; Shew et al., 2016). Arctic‐breeding birds such as barnacle geese experience a very short breeding season, as the snow‐free season is limited (mean snow‐free season length in Kongsfjorden is 81 days ± 12: Lameris et al., 2019) which seems to prohibit renesting (from laying till fledge takes approx.…”
Section: Discussionmentioning
confidence: 99%
“…Female barnacle geese plastically increased their nest defence over the season, as reflected by a decrease in their FID. Parental investment theory and the renesting potential hypothesis are two non-exclusive explanations for this pattern (see Introduction; Shew et al, 2016).…”
Section: Plastic Adjustment Of Nest Defence Behaviour To Changes In Assetmentioning
confidence: 99%
“…Most studies conclude that males defend nests more aggressively than females (Redmond et al 2009;Klvanova et al 2011;Svagelj et al 2012;Shew et al 2016) and this difference is attributed to the larger size of males compared with females in many species. Larger individuals should be able to defend nests either more efficiently or aggressively with less risk than their smaller counterparts (Wallin 1987).…”
Section: Differences In Nest Defense Between the Sexesmentioning
confidence: 99%
“…Second, if the focal gulls became habituated to simulated predation events, then we would expect to see a directional change in the aggressive responses over time. For instance, previous research with songbirds (Knight & Temple 1986;Shew et al 2016) and research in our study system (Burger & Gochfeld 1983) showed that birds repeatedly exposed to a human intrusion responded with increasingly bold behavior over time. Alternatively, if birds became accustomed to the intrusion and realized that no real danger existed, then we might expect a decrease in aggressive responses over time.…”
Section: Figmentioning
confidence: 64%